ENGINEERING PERSONNEL TRAINING THROUGH THE EXAMPLE OF VOLGA STATE UNUVERSITY OF TECHNOLOGY, MARI EL, RUSSIA - Romanov, Evgenii; Andrianov, Yuri; Nizova, Lyudmila; Nikitina, Anna (Journal of Applied Engineering Science, 2016)
The paper reveals priorities and problems of engineering personnel training through the example of Volga State University of Technology, Mari El, Russia. The article presents the following issues: dynamics of its innovative development, interaction between the university and employers, realization of strategic development programs, innovative infrastructure expansion, increase in activity of scientific students’ societies, creation of interregional resource and unique centres of shared use. On the basis of monitoring, social research of graduates-engineers and employers interviewing, we summarized experience in the field of interaction between students’ science and manufacture, elicited the reasons for imbalance of the regional labour market and the market of educational services. The paper determines new dimensions of cooperation between the university and enterprises, including the international level.